Congenital persistent infection with bovine viral diarrhea virus not observed in piglets - Gomes, Felipe S. [UNESP]; Mechler-Dreibi, Marina L. [UNESP]; Gatto, Igor R. H. [UNESP]; Storino, Gabriel Y. [UNESP]; Pires, Felipe F. B. [UNESP]; Xavier, Eduarda B. [UNESP]; Samara, Samir [UNESP]; Oliveira, Luis Guilherme de [UNESP] (Canadian Vet Med Assoc, 2019)
This study was designed to determine whether congenital persistent infection occurs in piglets from gilts experimentally inoculated with bovine viral diarrhea virus type 2 (BVDV-2). Six pregnant gilts were divided into 2 groups, infected (n = 4), and control (n = 2). The gilts were inoculated at 45 days gestation. Piglets were assessed for 35 days following birth with nasal swab and blood sample collections every 72 hours. Reverse transcriptase-polymerase chain reaction (RT-PCR) tests were performed for direct diagnosis of virus in blood and nasal swabs, and virus neutralization was used for antibody detection. Transplacental transmission of BVDV-2 did not occur. Piglets were born free of the virus and did not shed BVDV during the experimental period.